Emproved Z-Source Dynamic Voltage Restorer Based on the Minimum Energy. Issue 3 (October 2020) - Li, Yongxiang; Li, Mengda; Ma, Menglin
Abstract: Dynamic voltage restorer (DVR) is a good choice to solve voltage sag problem. Aiming at the shortcomings of traditional DVR, an improved DVR model is proposed. The improved DVR took H-bridge inverter as the main frame, and the energy storage unit was based on the battery. The coupling unit directly connected the capacitor in LC filter to the power grid instead of the transformer, and connected a Z-source network between the energy storage unit and the inverter unit to improve the voltage compensation range and eliminate the impact of the series transformer. Finally, by connecting a current compensation device in parallel on the load side, combined with the minimum energy compensation control strategy, the amplitude and phase of the load voltage compensated by the improved DVR device were consistent with that before the drop. A MATLAB / Simulink simulation model is built to verify the effectiveness of the proposed improved DVR. The simulation results verify the effectiveness of the proposed improved DVR.